Implementation of reading board media to improve early reading skills: an action research study in 1st grade at SD Negeri 47/IV Kota Jambi - Lestari, Olivia Indah; Nugraha, Ugi; Widowati, Atri (Universitas Kanjuruhan Malang, 2025)
Early reading skills are essential for elementary students, yet many struggle due to unengaging methods and limited media support. This study examines the effectiveness of reading board media in improving first graders’ reading abilities. Using Classroom Action Research (CAR) based on the Kemmis & McTaggart model, the research was conducted in two cycles. Data were collected through observations, reading tests, interviews, and documentation, then analyzed qualitatively and quantitatively. Results indicate significant improvement in students' reading skills. The first cycle increased students' interest and participation, while the second cycle enhanced fluency in reading words and simple sentences. The findings confirm that reading board media effectively boosts early reading skills and learning motivation. This interactive approach is recommended as an innovative literacy tool, supported by teacher training, parental involvement, and adequate facilities, to foster a more engaging and effective early reading experience.